Wnt/β-Catenin Pathway in Experimental Model of Fibromyalgia: Role of Hidrox® - Ramona D’Amico; Marika Cordaro; Rosalba Siracusa; Daniela Impellizzeri; Angela Trovato Salinaro; Maria Scuto; Maria Laura Ontario; Roberto Crea; Salvatore Cuzzocrea; Rosanna Di Paola; Roberta Fusco; Vittorio Calabrese (Biomedicines, 2021)
Fibromyalgia (FM) is a chronic condition characterized by persistent widespread pain that negatively affects the quality of life of patients. The WNT/β-catenin signaling pathway seems to be involved in central sensitization and different pain states. The objective of this study was to investigate the beneficial effects of a new compound called Hidrox® (HD), containing 40–50% hydroxytyrosol, in counteracting the pain associated with FM. An FM-like model was induced in rats by subcutaneous injections of reserpine (1 mg/kg) for three consecutive days. Later, HD (10 mg/kg) was administered orally to the animals for seven days. Reserpine injections induced WNT/β-catenin pathway activation, release of pro-inflammatory mediators as well as a significant increase in oxidative stress. Daily treatment with HD was able to modulate the WNT/β-catenin and Nrf2 pathways and consequently attenuate the behavioral deficits and microglia activation induced by reserpine injection. These results indicate that nutritional consumption of HD can be considered as a new therapeutic approach for human FM.